CARDIOVASCULAR PREVENTION: METABOLIC SYNDROME AND LIFESTYLE IN WOMEN, THE PROSA STUDY. (June 2018) - Meazza, R.; Scarpini, G.; Ferrari, G.; Ratti, A.; Schiavone, M.; Allievi, L.; Lombardi, F.; Villarini, A.
Abstract : Objective: Menopause is not a disease, but changing in hormonal status determines modifications in woman's metabolism with rising of new cardiovascular risk factors. It is well known that metabolic syndrome (MetS) after menopause is associated with an increased cardiovascular risk. Design and method: The PROSA (Prevention in Rosa) study is a randomized controlled trial designed to test the efficacy of dietary change and physical activity in preventing or delaying the development of CVS disease in patients estimated to be at high risk based on the presence of at least one MetS factor or in treatment for one of them. Participants were recruited through the Hypertension Unit of the University Hospital of Milan. 1032 women were randomized in two groups: 513 received standard recommendation for healthy lifestyle (ESC/AHA) without any active support (control group); 519 received standard recommendation and were invited to attend kitchen courses, gym and dance classes and reinforcing meetings (intervention group). The goal was to reduce MetS factors through lifestyle change. Results: The data show that each MetS factor can be modifiable by changing the lifestyle (table 1). Physical activity (moderate/intense) seems to improve MetS factor more strongly than nutritional changes. Daily consumption of plant foods (whole grains, pulses, vegetables and fruit) is more effective in modulating MetS compared to other indications. Figure. No caption available. Conclusions: In conclusion we observed that for cardiovascular prevention it is important to promote a daily physical activity (at least 30 min/day) and to increase consumption of plant foods before starting pharmacological treatment, because these lifestyle changes are able to modify MetS factors.